Neutron tomography using an elliptic focusing guide - Kardjilov, Nikolay; Hilger, A.; Dawson, M.; Manke, I.; Banhart, J.; Strobl, Markus; Böni, P. (Journal of applied physics, 2010)
An elliptic focusing neutron guide was combined with a cold neutron imaging instrument to produce a cone-beam, whose parameters were then characterized both at the focal point and at the detector position. This point source geometry provides improved experimental conditions for tomographic applications, providing a larger beam cross-section and enabling geometric magnification. The experimental data were compared with Monte Carlo simulations and both experiments and simulations demonstrate superior spectral and geometric homogeneity of the cone-beam setup compared to the conventional pinhole geometry.
Gesehen am 02.03.2023